(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to determine and understands the regulations regarding legal protection of the copyright of the art work of the Kreasi Baru Four Ethnic Dance in South Sulawesi. This study uses empirical legal research methods. The results showed that the guarantee of legal protection against the copyright of the new creations of dance creation by four ethnic groups of south Sulawesi has been regulated in Law Number 28 of 2014 concerning Copyright but has not been comprehensive. The recommendations from this study are the government as the implementer of the law can make implementing regulations in the form of regional regulations that regulate more comprehensively related to legal protection of the copyright of the new creative dance works of the four ethnic groups of South Sulawesi. Abstrak Penelitian ini bertujuan untuk mengetahui dan memahami pengaturan tentang perlindungan hukum terhadap hak cipta karya seni Tari Kreasi Baru Empat Etnis Sulawesi Selatan. Penelitian ini menggunakan metode penelitian hukum empiris. Hasil penelitian menunjukkan bahwa mengenai jaminan perlindungan hukum terhadap hak cipta karya seni tari kreasi baru empat etnis Sulawesi selatan telah diatur di dalam Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta namun belum komperhensif. Adapun rekomendasi dari penelitian ini agar pemerintah sebagai pelaksana undang-undang dapat membuat peraturan pelaksana berupa peraturan daerah yang mengatur lebih komperhensif terkait perlindungan hukum terhadap hak cipta karya seni tari kreasi baru empat etnis Sulawesi selatan.